Cardiovascular disease and depression in psoriatic arthritis: Multidimensional comorbidities requiring multidisciplinary management. Issue 2 (June 2021) - So, Ho; Tam, Lai-Shan
Abstract: Psoriatic arthritis (PsA) is a chronic systemic inflammatory disease. The control of joint and skin manifestations has improved tremendously with the advent of the targeted therapies in the past decade. However, the occurrence of PsA is frequently accompanied by metabolic diseases, cardiovascular diseases (CVD), and depression. They are often unrecognized or undertreated, which leads to significant morbidities and even mortality. PsA predisposes patients to these important commodities through a number of mechanisms and their complex interaction, including chronically overexpressed inflammatory cytokines, a high prevalence of traditional CVD risk factors, the impact of pharmacotherapies, and a significant psychological burden. Herein, we review and discuss evidence on the epidemiology, pathophysiology, and assessment of CVD as well as depression in patients with PsA. Lastly, a multidisciplinary management approach to this multifaceted disease is presented.